Synthesis and Characterization of Dodecylbenzene Sulfonic Acid doped Tetraaniline via Emulsion Polymerization - K. Basavaiah; K. Tirumala Rao; A. V. Prasada Rao (E-Journal of Chemistry)
In this work, we report preparation and characterization of dodecylbenzene sulfonic acid (DBSA) doped tetraaniline via micelles assisted method using ammonium per sulphate (APS) as an oxidant. Here, DBSA act as dopant as well as template for tetraaniline nanostructures. The synthesized DBSA doped tetraaniline have been well characterized by X-ray diffraction patterns, Fourier transform infrared spectroscopy, UV-Visible spectroscopy, Scanning electron microscopy and thermogravimetry. The morphologies of tetraaniline were found to be dependent on molar ratios of N-phenyl-1, 4-phenylenediamine to DBSA. The spectroscopic data indicated that DBSA doped tetraaniline. Thermogravimetry studies revealed that the DBSA doping improved the thermal stability of tetraaniline.